PADI2 Polymorphisms Are Significantly Associated With Rheumatoid Arthritis, Autoantibodies Serologic Status and Joint Damage in Women from Southern Mexico - Guzmán-Guzmán, Iris Paola; Ramírez-Vélez, Claudia Isabel; Falfán-Valencia, Ramcés; Navarro-Zarza, José Eduardo; Gutiérrez-Pérez, Ilse Adriana; Zaragoza-García, Oscar; Ramírez, Mónica; Castro-Alarcón, Natividad; Parra-Rojas, Isela (Frontiers in Immunology, 2021)
The enzymes of the family peptidylarginine deiminases (PADIs) have an important role in the pathogenesis of rheumatoid arthritis (RA) due to their association with the anti-citrullinated protein antibodies (ACPA) production. To evaluate the association between single-nucleotide polymorphisms (SNPs) in the PADI2 gene and RA susceptibility, related clinical parameters, and the serologic status of autoantibodies in a women population with RA from southern Mexico, a case-control study was conducted (case n=229; control n=333). Sociodemographic characteristics were evaluated, along with clinical parameters, inflammation markers, the levels of ACPAs as anti-cyclic citrullinated peptides (anti-CCPs), anti-modified citrullinated vimentin (anti-MCV), and rheumatoid factor (RF). Genomic DNA was extracted from peripheral blood, and three SNPs of the PADI2 gene (rs1005753, rs2057094, and rs2235926) were performed by qPCR using TaqMan probes. The carriers of the T allele for rs2057094 and rs2235926 presented an earlier onset of the disease (β= -3.26; p = 0.03 and β = -4.13; p = 0.015, respectively) while the carriers of the T allele for rs1005753 presented higher levels of anti-CCPs (β= 68.3; p = 0.015). Additionally, the T allele of rs2235926 was associated with a positive RF (OR = 2.90; p = 0.04), anti-MCV (OR = 2.92; p = 0.05), and with the serologic status anti-CCP+/anti-MCV+ (OR = 3.02; p = 0.03), and anti-CCP+/anti-MCV+/RF+ (OR = 3.79; p = 0.004). The haplotypes GTT (OR =1.52; p = 0.027) and TTT (OR = 1.32; p = 0.025) were associated with the presence of RA. In addition, the haplotype TTT has been linked to the presence of radiographic joint damage with the Sharp-van der Heijde score (SHS) ≥2 (OR = 1.97; p = 0.0021) and SHS ≥3 (OR = 1.94; p = 0.011). The haplotype TTT of SNPs rs1005753, rs2057094, and rs2235926 of the PADI2 gene confers genetic susceptibility to RA and radiographic joint damage in women from southern Mexico. The evidence reveals that SNPs of the PADI2 gene favors the presence of a positive serologic status in multiple autoantibodies and the clinical manifestations of RA at an early onset age.